Real-world treatment patterns and clinical outcomes among elderly patients with locoregionally advanced head and neck squamous cell carcinoma in the United States - Zheng, Dandan; Zhang, Su; Bidadi, Behzad; Lerman, Nati; Song, Yan; Song, Rui; Li, Jiayang; Zhu, Anyu; Tang, Yuexin; Signorovitch, James; Merchant, Sanjay; Hanna, Glenn J. (Frontiers in Oncology, 2025)
IntroductionMultimodal therapy, including resection followed by adjuvant radiotherapy (RT) ± systemic therapy (ST) or definitive RT ± ST, is typically recommended for patients with locoregionally advanced head and neck squamous cell carcinoma (LA HNSCC) treated with curative intent. We assessed the real-world use of various treatment modalities and associated survival outcomes among elderly patients with LA HNSCC who received surgical or non-surgical primary treatment.MethodsLinked SEER-Medicare data were used in this retrospective cohort study. Patients with newly diagnosed stage III-IVB LA HNSCC (larynx, hypopharynx, oral cavity, or oropharynx) from 2007–2019 who received primary treatment within 4 months after initial diagnosis were included. Real-world event-free survival (rwEFS) and overall survival (rwOS) from the index date (primary treatment initiation date) were described using Kaplan-Meier estimates. The correlation between rwEFS and rwOS was investigated by normal scores rank. Landmark analysis was conducted using Cox proportional hazards models to compare rwOS between patients with versus without recurrence in the first year after primary treatment initiation.ResultsOf 2180 patients meeting the selection criteria, 626 and 1554 were categorized into the resected and unresected cohorts, respectively (median follow-up: 20.8 and 22.6 months). Overall, the mean age at initial diagnosis was 74.3 years, 65.9% were male, and 81.7% were White. More than half (56.3%) of the patients with resected tumors received RT ± ST post-surgery while nearly two-thirds (64.9%) of those with unresected tumors received definitive RT+ST. The resected cohort had a median rwEFS of 7.8 (95% confidence interval [CI]: 6.4, 8.7) months and a median rwOS of 31.4 (95% CI: 25.2, 40.1) months. The unresected cohort had a median rwEFS of 10.0 (95% CI: 9.4, 10.9) months and a median rwOS of 32.4 (95% CI: 28.5, 36.7) months. There was a significant positive correlation between rwEFS and rwOS for both the resected (r [95% CI]: 0.69 [0.63, 0.73]) and unresected (0.68 [0.63, 0.73]) cohorts (both p<0.001). In the resected cohort, there was a trend of lower rwOS among patients who experienced recurrence within the first year post-index as compared with those without recurrence (adjusted hazard ratio [95% CI]: 1.31 [0.96, 1.80]), whereas in the unresected cohort, the association was significant (1.91 [1.60, 2.29]).ConclusionIn elderly patients with LA HNSCC, surgery followed by RT and definitive RT+ST were the most common treatment modalities in the resected and unresected cohorts, respectively. The suboptimal real-world survival of both groups highlights the significant unmet need for more effective therapies. The positive associations between rwEFS and rwOS in both the resected and unresected cohorts support EFS as a predictor of OS when OS data are immature in LA HNSCC.